Synthesis, structure and magnetic properties of La3Co2SbO9: A double perovskite with competing antiferromagnetic and ferromagnetic interactions - Franco, D.G. (2012)
Fil: Sánchez, R.D. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina